Rasio Bobot Hepar-Tubuh Mencit (Mus musculus L.) setelah Pemberian Diazepam, Formalin, dan Minuman Beralkohol - W, Arief Niendya; Djaelani, Muhammad Anwar; Suprihatin, Teguh (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
Drugs abuse and addictive compound were increasing. The drugs abuse and compound non food itself are diazepam, formaldehyde and alcohol which can generate negative impact to human. The effect of diazepam in body can pressure nerve system meanwhile, effect in liver-body mass ratio is increasing ratio as respon at toxic which is entering the body. Alcohol effect in liver can make lipid deposition in liver. The effect of formalin can initiate damage to liver caused toxic compound. Mice (Mus musculus) were used as animal test to show the damage excessive dose of giving diazepam, formalin, and alcohol to liver-body mass ratio in mice. The benefit of this research is give information about influence of treatment diazepam, formaldehyde and alcohol at liver-body mass of mice. The method of treatment used complete random plan which is divided into four groups of treatment, repeating four times each group. Group P0 (aquadest as control) P1 (diazepam 0. 04 mg) P2 (formaldehyde 0. 01%) P3 (alcohol 4.8%). The research spent 1 month, six days for acclimatization and 24 days for treatment period. The data was analyzed with anova. The result showed that three compounds was not significant different compared with control. It was happened becaused metabolism of diazepam, formaldehyde and alcohol can do perfectly in the liver, so it was not affected the liver-body mass ratio. The conclusion diazepam, formaldehyde and alcohol was not influence the liver-body mass which showed physiological process in mice related to metabolism process in produce food reserve.